2018
DOI: 10.1098/rsif.2018.0473
|View full text |Cite
|
Sign up to set email alerts
|

Passive bristling of mako shark scales in reversing flows

Abstract: Shark skin has been shown to reduce drag in turbulent boundary layer flows, but the flow control mechanisms by which it does so are not well understood. Drag reduction has generally been attributed to static effects of scale surface morphology, but possible drag reduction effects of passive or active scale actuation, or 'bristling', have been recognized more recently.Here, we provide the first direct documentation of passive scale bristling due to reversing, turbulent boundary layer flows. We recorded and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…5 The reason for the passive bristling of shark denticles in reversing the ows has been described by Du Clos et al, who explained the downward backow between the denticles and the vortex above the denticles were associated with passive bristling by a high-speed camera. 50 Some adverse factors, such as backow, can be inhibited by the passive bristling of shark denticles. The study suggested that shark skin denticles may absorb the negative energy of backow by passive bristling and delay the onset of turbulence in the boundary layer.…”
Section: ) 41mentioning
confidence: 99%
“…5 The reason for the passive bristling of shark denticles in reversing the ows has been described by Du Clos et al, who explained the downward backow between the denticles and the vortex above the denticles were associated with passive bristling by a high-speed camera. 50 Some adverse factors, such as backow, can be inhibited by the passive bristling of shark denticles. The study suggested that shark skin denticles may absorb the negative energy of backow by passive bristling and delay the onset of turbulence in the boundary layer.…”
Section: ) 41mentioning
confidence: 99%
“…The first is that riblets can reduce momentum transfer and shear stress by preventing cross-flow over the scales ( Bechert et al, 2000b ). The second is that the scales are flexible and capable of bristling to stop reversed flow across the skin surface ( Lang et al, 2011 ; Du Clos et al, 2018 ; Santos et al, 2021 ). NASA Langley Research Center ( Walsh and Weinstein, 1978 ) has carried out research on the drag reduction performance of ribbed surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…One function that has been an important focus for research is the role of denticles in support of locomotion, as many extant shark species have denticles with morphologies that improve swimming performance. Fluid dynamic studies have revealed that denticles can improve swimming performance by enhancing thrust, reducing hydrodynamic drag, as well as changing the boundary layer characteristics of water flow over the body ( DuClos et al. 2018 ; Lang et al.…”
Section: Introductionmentioning
confidence: 99%